Pengaruh Model Problem Based Learning (PBL) Berbantuan Media Baamboozle Terhadap Hasil Belajar PKn Siswa Kelas IV Sekolah Dasar - Sari, Novi; Ramadan, Zaka Hadikusuma (Jayapangus Press, 2025)
Students' cognitive understanding of Civic Education (PKn) subject matter is still relatively low, which is one of the fundamental problems in the learning process in elementary schools. This condition is caused by several factors, such as the lack of active student involvement, monotonous learning methods, and minimal use of interesting and interactive media. The purpose of this study was to describe the effect of the Problem Based Learning (PBL) model assisted by Baamboozle media on the learning outcomes of Civic Education students in grade IV of SDN 14 Pekanbaru. This study used a Pre-Experimental design with the form of One Group Pretest and Posttest. This study involved a sample of 24 students from grade IV of SDN 14 Pekanbaru. Data collection techniques were collected through multiple-choice test questions analyzed by paired sample t-test and simple linear regression. The results of the paired sample t-test showed an average pretest of 63.08 and a posttest of 80.92. Based on the decision-making criteria for the paired sample t-test, sig. p <0.05, then Ho is rejected and Ha is accepted. Analysis using a simple linear regression test obtained an R Square value of 0.898 or 89.8%. The Baamboozle-assisted PBL model has proven to be an effective effort to improve civics learning outcomes, especially in elementary schools. The novelty of this study lies in the integration of the PBL learning model that focuses on solving real problems collaboratively with the interactive and interesting Baamboozle educational game media. The implication of this finding is that teachers, especially at the elementary school level, need to consider using more innovative and interactive learning approaches to increase students' cognitive engagement and understanding of abstract and conceptual civics material.